Association Between Serum Uric Acid Level and Carotid Atherosclerosis and Metabolic Syndrome in Patients With Type 2 Diabetes Mellitus - Li, Wei; Wang, Yan; Ouyang, Shengrong; Li, Mengdi; Liu, Rui; Zhang, Yuqi; Liu, Xiaojun; Li, Tianfang; Liu, Shengyun (Frontiers in Endocrinology, 2022)
Background Serum uric acid (SUA) is associated with many cardiovascular risk factors, such as metabolic syndrome (MetS) and subclinical atherosclerosis. However, the relationship of SUA with carotid atherosclerosis remains controversial. We aimed to investigate whether elevated SUA levels are associated with a high risk of carotid atherosclerosis and MetS in patients with type 2 diabetes mellitus (T2DM). Methods This cross-sectional study was performed with a sample of 1,947 hospitalized patients with T2DM. Carotid intima-media thickness and carotid artery plaques were measured via Doppler ultrasound. Results Uric acid levels were negatively associated with HbA1C, eGFR, and HDL-C (all P < 0.001) and positively associated with WBC, BMI, ACR, creatinine, total cholesterol, triglycerides, LDL-C, systolic blood pressure, and diastolic blood pressure (all P < 0.001). After adjusting for multiple potential confounders, the risks were substantially higher for MetS in the highest quartile of SUA levels (odds ratio: 2.91, 95% confidence interval: 1.54–5.51, P = 0.003 for trend) than in the lowest quartile of SUA levels. Furthermore, a significant increase was observed in the prevalence of overweight/obesity, hypertension, and dyslipidemia across the SUA quartiles independent of confounders. However, no significant association was found between SUA quartile with the presence of carotid atherosclerosis. Conclusions In patients with T2DM, SUA levels were closely associated with MetS and its components but not with carotid atherosclerosis.